Implementasi Metode Simple Additive Weighting untuk Menentukan Kriteria Guru Terbaik Di Smak St. Albertus Malang - Subekti, Puji; Henry, Rivaldo (Institut Tekonologi dan Binisi Asia Malang, 2024)
Indonesia's education continues to experience commendable ranking improvements. Nevertheless, societal demands for educational quality in schools are increasingly pressuring institutions to compete in producing the best graduates. Generating high-achieving students requires high-quality educators. Therefore, a system capable of precise calculation with weighting and top priorities is necessary. One technique that can be utilized is the Simple Additive Weighting. The Simple Additive Weighting method is appropriate for addressing this issue because it enhances the accuracy of calculations by multiplying the weights of different criteria. The initial input consists of raw scores of teachers across various criteria in the school. Subsequently, Simple Additive Weighting calculates the overall assessment and displays the ranking of teachers in the school.